2020
DOI: 10.30845/ijbss.v11n5a9
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Corporate Sustainable Development: Evidence from Greece

Abstract: This study investigates the relationship between organizational culture and corporate sustainable development (CSD).Organizational culture is measured based on the four types of culture of the competing values framework: i) clan, ii) adhocracy, iii) hierarchy and iv) market type, while CSD was examined as a construct of i) economic, ii) environmental and iii) social dimension. The survey on medium-and large-sized firms in Greece reveals that adhocracy and hierarchy type of organizational culture have a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This is a multidimensional topic given that the extant literature thus far follows two main strands focussing on the critical aspects of sociology and anthropology and several economic, environmental and social dimensions of sustainability. This study is consistent with similar studies on cultural values and their relationships with different aspects of businesses (Deirmentzoglou et al , 2020; Kim and Kim, 2010; Scholtens and Dam, 2007). However, it differentiates itself from and contributes to the literature by examining the critical role of cultural values in the perceptions of the three aspects of corporate SD (CSD): economic, social and environmental.…”
Section: Introductionsupporting
confidence: 93%
“…This is a multidimensional topic given that the extant literature thus far follows two main strands focussing on the critical aspects of sociology and anthropology and several economic, environmental and social dimensions of sustainability. This study is consistent with similar studies on cultural values and their relationships with different aspects of businesses (Deirmentzoglou et al , 2020; Kim and Kim, 2010; Scholtens and Dam, 2007). However, it differentiates itself from and contributes to the literature by examining the critical role of cultural values in the perceptions of the three aspects of corporate SD (CSD): economic, social and environmental.…”
Section: Introductionsupporting
confidence: 93%
“…Sustainability also entails adapting to change while maintaining system identity (Fok et al 2023). Deirmentzoglou et al (2020), argued that Sustainability poses a challenge in terms of implementation, as it involves various factors, including society, economics, and the environment. Sustainable development was defined as an improvement that satisfies present needs while not impairing the ability of the next generation to fulfill their own demands (Deirmentzoglou et al, 2020).…”
Section: Literature Review Sustainability Practicesmentioning
confidence: 99%
“…To enhance organizational performance and comprehend the influence of organizational culture on personnel, it is imperative to gain a comprehensive understanding of how organizational culture directly influences the success of an organization (Cura, 2018). Researchers suggested that an adequate organizational culture may contribute to a path for businesses' sustainable growth (e.g., Deirmentzoglou et al, 2020). The effective establishment of a culture centered around sustainability will yield optimal benefits for society, the economy, and the environment (Deirmentzoglou et al, 2020).…”
Section: Organizational Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Shane [28] underlines that countries need to promote those cultural values that encourage innovation while stating that investing in research and development is a required but not sufficient condition for improvements in innovation performance. On the same strand, Deirmentzoglou et al [29,30] investigate the influence of culture on sustainable development.…”
Section: Introductionmentioning
confidence: 99%